Perpendicular magnetic anisotropy in Co–Pt granular multilayers - Bartolomé, J.; Figueroa, A.I.; García, L.M.; Bartolomé, F.; Ruiz, L.; González-Calbet, J.M.; Petroff, F.; Deranlot, C.; Wilhelm, F.; Rogalev, A.; Brookes, N. (Физика низких температур, 2012)
Magnetization hysteresis curves have been measured on Co granular multilayers, (Al₂O₃/Co/Pt)N (N = 1 and 25), with the applied magnetic field parallel and perpendicular to the substrate plane. In all samples perpendicular magnetic anisotropy was observed. For Co particles with average diameter 3 nm, the coercive field at low temperature is μ₀HC = 0.5 T. HC decreases for increasing temperature and disappears at ≈200 K. A soft magnetic component is also present in all samples up to the freezing temperature Tf = 365 K. Co and Pt XMCD measurements at the L2,3 edges were performed, yielding to the orbital mL and spin mS contributions to the total magnetic moment of the system. These results, in addition to XANES ones, indicate the presence of CoxPt₁₋x alloy. Particles conformed of CoPt alloy, embedded in Pt and coupled magnetically by dipolar or RKKY interaction, may explain the phenomenology observed in these systems.